Altitude training 2 (2000)
This is the Coaching Science Abstracts volume 5(4): February, 2000: ALTITUDE TRAINING 2 This is the second issue that reviews 30 articles concerned with altitude training. It adds to the abstracts presented in Volume 2(4).